Platonic mysticism: contemplative science, philosophy, literature, and art - Versluis, Arthur (Series in Western esoteric traditions, 2017)
Platonic mysticism -- Mapping mysticism -- The eclipse of Platonic mysticism -- The externalist fallacy -- On literature and mysticism -- Transcendence -- Contemplative art, contemplative science